(untitled) (Archives of Criminology, 2023)
The concept of a restorative city is one of the most recent successful developments in the field of restorative justice theory and practice. Despite the lack of universal standards of implementation, a restorative city can be defined as a process that aims to shape both community life as well as urban space through the lens of restorative justice philosophy, values, and standards. The purpose of this article is to discuss the results of the analysis of how this concept has been implemented in the following cities: Hull (United Kingdom), Bristol (United Kingdom), Brighton & Hove (United Kingdom), Leuven (Belgium), Como (Italy), Tempio Pausania (Italy), Whanganui (New Zealand) and Oakland (United States). The article concludes with a brief summary of activities that have been undertaken in Wrocław in order to gain the status of a restorative city.